THE EFFECT OF GALLERY WALK ON STUDENTS’ WRITING ANNOUNCEMENT (A Study at the Tenth Grade of SMK Negeri 1 Lumut 2018/2019 Academic Year) - kamisah S.Pd M.Pd (Institut Pendidikan Tapanuli Selatan, 2019)
The purpose of this research are to find out: 1) The application of gallery walk on students’ writing announcement. 2) The students’ writing announcement before and after using gallery walk. 3) Whether there is a significant effect of gallery walk on the students’ writing announcement at the tenth grade of SMK Negeri 1 Lumut. Method of the research is experimental. The population of this research are all of the tenth grade students of SMK Negeri 1 Lumut that consists of 119 students. Purposive sampling technique is used to get the sample of research , the sample consist of 30 students. The technique for collecting data are observation sheet and test. The result of the application of gallery walk is 3.68 categorized “Very Good”. Before using Gallery Walk is 54. 2 categorized “Low”. Meanwhile, after using Gallery Walk is 76.56 categorized “Good”. The result of ttest 13.75 and ttable 2.04 it means that there is any significant effect of using Gallery Walk on students’ writing announcement at the tenth grade SMK Negeri 1 Lumut 2018/2019 Academic Year.